2014
DOI: 10.1002/aur.1398
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Brain Function Underlying Inhibitory Control in Autism Spectrum Disorders

Abstract: The development of inhibitory control—the ability to suppress inappropriate actions in order to make goal-directed responses—is often impaired in autism spectrum disorders (ASD). In the present study, we examined whether the impairments in inhibitory control evident in ASD reflect—in part—differences in the development of the neural substrates of inhibitory control from adolescence into adulthood. We conducted a functional magnetic resonance imaging (fMRI) study on the anti-saccade task, a probe of inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 81 publications
3
31
0
Order By: Relevance
“…Extending previous findings (Padmanabhan et al., ), we found that for both ASD and control groups, the abilities to inhibit responses and proactively delay response onset mature into early adulthood. Stopping abilities mature rapidly from middle childhood and throughout adulthood in individuals with and without ASD, consistent with previous findings (Happe et al., ; Luna et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…Extending previous findings (Padmanabhan et al., ), we found that for both ASD and control groups, the abilities to inhibit responses and proactively delay response onset mature into early adulthood. Stopping abilities mature rapidly from middle childhood and throughout adulthood in individuals with and without ASD, consistent with previous findings (Happe et al., ; Luna et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest the importance of these skills to socio-emotional adjustment and vice versa. Although inhibition deficits characterize children with ASD (Padmanabhan et al 2014) which was corroborated in this study, these deficits were only associated with one form of socio-emotional adjustment (i.e., depressive symptoms) in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, research has consistently shown that youth with HFASD demonstrate impairments in EF in comparison to neurotypical peers (Akshoomoff 2005;Hughes 2011;Russo et al 2007;Semrud-Clikeman et al 2014;Verte et al 2006) and those with Attention-Deficit/Hyperactivity Disorder (ADHD; e.g., Semrud-Clikeman et al 2010;Hughes 2011). EF include a variety of higher order cognitive skills, but inhibition and emotional control are thought to be especially pertinent to social and emotional functioning (Padmanabhan et al 2014;Riggs et al 2006). Indeed, existing literature suggests that deficits in inhibition and emotional control have been reported among children and adolescents with ASD (Konstantareas and Stewart 2006;Verte et al 2006;Narzisi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Activation in both the left and right dACC predicted RBs. Finally, Padmanabhan et al [93] used fMRI to extend Luna et al’s [85] behavioral study of cognitive control using an anti-saccade task. The groups did not differ in pro-saccade performance.…”
Section: Components Of the Scaffoldmentioning
confidence: 99%